2019
DOI: 10.1111/dom.13922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dapagliflozin in Japanese patients with inadequately controlled type 1 diabetes (DEPICT‐5): 52‐week results from a randomized, open‐label, phase III clinical trial

Abstract: Aims To investigate the safety and tolerability of 5 and 10 mg dapagliflozin added to insulin therapy over 52 weeks in Japanese patients with inadequately controlled type 1 diabetes mellitus (T1DM). Materials and methods This randomized, open‐label, parallel‐group, multicentre phase III clinical trial was conducted from October 26, 2015 to June 15, 2017. The primary endpoint was the occurrence of adverse events such as hypoglycaemia and diabetic ketoacidosis. Secondary endpoints included changes in glycaemic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
5
11
1
Order By: Relevance
“…25 A reduction in HbA1c was observed at week 24 following treatment with 5 or 10 mg dapagliflozin, and reduced HbA1c was observed up to week 52 for both doses with a similar safety profile to that observed in the current study. Taken together, the findings from the safety study 25 and the results of the current analysis support the overall favourable benefitrisk profile of dapagliflozin for the treatment of Japanese patients with T1D.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…25 A reduction in HbA1c was observed at week 24 following treatment with 5 or 10 mg dapagliflozin, and reduced HbA1c was observed up to week 52 for both doses with a similar safety profile to that observed in the current study. Taken together, the findings from the safety study 25 and the results of the current analysis support the overall favourable benefitrisk profile of dapagliflozin for the treatment of Japanese patients with T1D.…”
Section: Discussionsupporting
confidence: 82%
“…The frequencies of AEs and SAEs were higher in the dapagliflozin groups compared with the placebo group, which was similar to the pattern observed in the overall population. The AE profile was consistent with that known for dapagliflozin, 26 although DKA events were more frequently observed in the T1D than in the T2D population. In the Japanese subpopulation of the study, DKA events were observed in three patients receiving dapagliflozin.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical trials conducted in Japan and other countries have reported that the use of SGLT2-I for T1DM is associated with the risk of diabetic ketoacidosis (DKA) [8,9,16,17]. SGLT2-I increases glucagon production through urinary glucose excretion and its direct action on pancreatic α cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese Expert Committee further stated that a clinical trial of dapagliflozin in Japanese T1DM patients showed that patients with a BMI of less than 25 kg/m 2 had a higher incidence of DKA than patients with a BMI of 25 kg/ m 2 or more (occurrence rate%; BMI ≤ 25 kg/m 2 : 4.5%, BMI> 25 kg/m 2 : 0%). It was announced that extreme caution should be exercised when administering SGLT2 inhibitors to Japanese T1DM patients [14]. It has been pointed out that both patients and medical staff need to be educated to prevent risk, but it is very difficult to completely prevent DKA.…”
Section: Trials and Recommendationsmentioning
confidence: 99%